A study based on perception of first phase undergraduate medical students and faculty on integrated teaching in anatomy - Sudipto Konar; Sreetama Sarkar; Maloy Kumar Mondal; Prerana Aggarwal (Wolters Kluwer Medknow Publications, 2023)
Background: Integrated teaching has been recognized by the National Medical Commission as an effective method for enhancing knowledge and clinical correlation abilities among undergraduate medical students. This study aimed to assess the perceptions of first-phase undergraduate medical students and faculty toward the vertically integrated teaching-learning sessions in anatomy. Methodology: Three sessions of shared integration were conducted in the department of anatomy, involving the departments of surgery and orthopedics. After completion of the sessions, 147 students and 47 faculty members filled out prevalidated questionnaires to assess their perception of the integrated sessions. Feedback from the faculty was also taken. Statistical analysis was done by expressing the responses to the questionnaire on the five-point Likert scale as frequencies. Results: More than 85% of the students and faculty found these sessions engaging, interesting, and useful for understanding clinical problems related to anatomy. The students and faculty perceived the knowledge gained during these sessions as beneficial for answering university examination questions and for future clinical phases. However, 66% of the faculty expressed concerns about the time and coordination required for these sessions, and 89% considered arranging them challenging due to limited workforce availability. Conclusion: The findings indicate that undergraduate medical students perceive integrated teaching as a practical approach for acquiring anatomical knowledge and correlating it with the clinical aspects of a problem. Faculty members also acknowledged the usefulness of these sessions, but the challenges of regular arrangement were also highlighted. These results emphasize the importance of balancing clinical and anatomical education and provide insights for implementing integrated teaching strategies in the undergraduate medical curriculum.